Role of Class III phosphoinositide 3‐kinase in the brain development: possible involvement in specific learning disorders. (19th September 2016) - Inaguma, Yutaka; Matsumoto, Ayumi; Noda, Mariko; Tabata, Hidenori; Maeda, Akihiko; Goto, Masahide; Usui, Daisuke; Jimbo, Eriko F.; Kikkawa, Kiyoshi; Ohtsuki, Mamitaro; Momoi, Mariko Y.; Osaka, Hitoshi; et al.
Abstract: Class III phosphoinositide 3‐kinase (PIK3C3 or mammalian vacuolar protein sorting 34 homolog, Vps34) regulates vesicular trafficking, autophagy, and nutrient sensing. Recently, we reported that PIK3C3 is expressed in mouse cerebral cortex throughout the developmental process, especially at early embryonic stage. We thus examined the role of PIK3C3 in the development of the mouse cerebral cortex. Acute silencing of PIK3C3 with in utero electroporation method caused positional defects of excitatory neurons during corticogenesis. Time‐lapse imaging revealed that the abnormal positioning was at least partially because of the reduced migration velocity. When PIK3C3 was silenced in cortical neurons in one hemisphere, axon extension to the contralateral hemisphere was also delayed. These aberrant phenotypes were rescued by RNAi‐resistant PIK3C3. Notably, knockdown of PIK3C3 did not affect the cell cycle of neuronal progenitors and stem cells at the ventricular zone. Taken together, PIK3C3 was thought to play a crucial role in corticogenesis through the regulation of excitatory neuron migration and axon extension. Meanwhile, when we performed comparative genomic hybridization on a patient with specific learning disorders, a 107 Kb‐deletion was identified on 18q12.3 (nt. 39554147–39661206) that encompasses exons 5–23 of PIK3C3 . Notably, the above aberrant migration and axon growth phenotypes were not rescued by the disease‐related truncation mutant (172 amino acids) lacking the C‐terminal kinase domain. Thus, functional defects of PIK3C3 might impair corticogenesis and relate to the pathophysiology of specific learning disorders and other neurodevelopmental disorders. Acute knockdown of Class III phosphoinositide 3‐kinase (PIK3C3) evokes migration defects of excitatory neurons during corticogenesis. PIK3C3‐knockdown also disrupts axon outgrowth, but not progenitor proliferation in vivo . Involvement of PIK3C3 in neurodevelopmental disorders might be an interesting future subject since a deletion mutation in PIK3C3 was detected in a patient with specific learning disorders (SLD). Abstract : Acute knockdown of Class III phosphoinositide 3‐kinase (PIK3C3) evokes migration defects of excitatory neurons during corticogenesis. PIK3C3‐knockdown also disrupts axon outgrowth, but not progenitor proliferation in vivo . Involvement of PIK3C3 in neurodevelopmental disorders might be an interesting future subject since a deletion mutation in PIK3C3 was detected in a patient with specific learning disorders (SLD).